Embracing AI in Academia: Exploring University Teachers' Perspectives on Technology Integration in Pakistan - Bibi, Haleema; Shahzad, Mubbsher; Jan, Rahim; Majoka, Muhammad Iqbal (CV. Bimbingan Belajar Assyfa, 2025)
The rapid development of artificial intelligence (AI) in higher education demands a comprehensive understanding of university teachers' readiness and attitudes towards integrating this technology, particularly in the development of innovative learning media. This study aims to explore the beliefs and attitudes of university teachers in Pakistan towards the adoption of AI in teaching practices and examine its implications for the development and integration of technology-based learning media. The study employs a quantitative approach with a structured survey involving 250 teachers from various public and private universities in Pakistan, and the data is analyzed using descriptive statistics and the Chi-square test. The findings indicate that the majority of teachers recognize the potential of AI in enhancing teaching effectiveness, accelerating data analysis, and supporting the development of adaptive learning media. However, significant concerns remain regarding ethical issues, data privacy, and technology adoption readiness. These findings underscore the importance of continuous professional development, the formulation of ethical guidelines, and research collaboration to ensure the optimal integration of AI, contributing to the transformation of learning in higher education, particularly in the development of innovative and ethical learning media.